US Public Sexually Transmitted Disease Clinical Services in an Era of Declining Public Health Funding: 2013–14. Issue 8 (August 2017) - Leichliter, Jami S.; Heyer, Kate; Peterman, Thomas A.; Habel, Melissa A.; Brookmeyer, Kathryn A.; Arnold Pang, Stephanie S.; Stenger, Mark R.; Weiss, Gretchen; Gift, Thomas L.
Abstract : Background: We examined the infrastructure for US public sexually transmitted disease (STD) clinical services. Methods: In 2013 to 2014, we surveyed 331 of 1225 local health departments (LHDs) who either reported providing STD testing/treatment in the 2010 National Profile of Local Health Departments survey or were the 50 local areas with the highest STD cases or rates. The sample was stratified by jurisdiction population size. We examined the primary referral clinics for STDs, the services offered and the impact of budget cuts (limited to government funding only). Data were analyzed using SAS, and analyses were weighted for nonresponse. Results: Twenty-two percent of LHDs cited a specialty STD clinic as their primary referral for STD services; this increased to 53.5% of LHDs when combination STD-family planning clinics were included. The majority of LHDs (62.8%) referred to clinics providing same-day services. Sexually transmitted disease clinics more frequently offered extragenital testing for chlamydia and/or gonorrhea (74.7%) and gonorrhea culture (68.5%) than other clinics (52.9%, 46.2%, respectively; P < 0.05). The majority of LHDs (61.5%) reported recent budget cuts. Of those with decreased budgets, the most common impacts were fewer clinic hours (42.8%; 95% confidence interval [CI], 24.4–61.2), reduced routine screening (40.2%; 95% CI, 21.7–58.8) and reductions in partner services (42.1%; 95% CI, 23.6–60.7). One quarter of those with reduced STD budgets increased fees or copays for clients. Conclusions: Findings demonstrate gaps and reductions in US public STD services including clinical services that play an important role in reducing disease transmission. Furthermore, STD clinics tended to offer more specialized STD services than other public clinics. Abstract : A survey of local health departments found gaps and reductions in US public sexually transmitted disease (STD) clinical services. Generally, STD clinics offered more specialized STD services than other safety net clinics.